Growth and Survival of Ripon Barbel (Barbus Altianalis) Larvae and Juveniles Fed Five Experimental Diets in Captivity - Aruho, Cassius; Walakira, John K.; Owori-Wadunde, Akisoferi; Nuwamanya, Ephraim; Bugenyi, Fred; Sserwadda, Martin; Rutaisire, Justus; Borski, Russell J. (Aquaculture Reports, 2020)
Mass production of quality seed is vital for commercial culture and requires prior knowledge of appropriate larval diets and their utilization. Four experiments were sequentially conducted at different periods to evaluate the effect of live and a processed microdiet on growth and survival of Barbus altianalis larvae and juveniles. Larvae were fed exclusively on live prey (Moina and Artemia nauplii), microdiet (57 % Crude Protein), decapsulated Artemia cysts and in combination (Moina + microdiet). The effect on growth was further evaluated in subsequent juvenile trial by co-feeding. Green water effect on larval growth was also evaluated. In the final experiment, 15 day old larvae were raised in fertilized outdoor concrete tanks. Results indicated that each diet affected larval growth significantly different (P < 0.05) with the combination diet (152.05 ± 2.51mg) and decapsulated Artemia (141.14 ± 2.43 mg) performing better than microdiet, Moina and Artemia nauplii in that order. In subsequent juvenile experiment, larvae originally fed decapsulated Artemia (510.13 ± 11.93 mg) and those fed a mixed diet (500.20 ± 11.8 mg) performed better than other diets. Ontogenetic pattern of amylase, lipase and protease activity identified larvae maturation age at 14–21 Days after hatching (DAH) (14.93 ± 0.36–31.5 ± 0.61 mg) with the combination diet. When larvae at 15 DAH were nursed in outdoor tanks, final survival and growth performance increased to 95.3 % and 1112 ± 42.70 mg compared to the indoor nursing at 90.9 % and 355.33 ± 6.44 mg respectively by 75 DAH. Therefore we recommend that any microdiet manipulations and or outdoor nursing be done during or after this period. Microalgae had no direct effect on larval growth (P > 0.05). In this study, larvae were confirmed to utilize the microdiet from exogenous stage but co-feeding produced best average weight (152.05 ± 2.51mg), specific growth rates (4.06 ± 0.19) and survival (90.9 %). This study provided guiding strategies for improved rearing of B. altianalis fingerlings in captivity.
Keywords: Larval diets; Weaning; Enzyme activity